Evolution in the perception of students between 6 and 13 years of age on citizenship: Peruvian context. - Mendoza-León, Olga Estela; Burgos -Goicochea, Saby; Pajuelo- Abanto, Miluska Jackeline Madelaine; Rodríguez- Albán, Segundo Miguel; Pérez- Mena, Celina (Journal of Posthumanism, 2025)
Citizenship is a fundamental pillar in the integral development of individuals within contemporary democracies, since it allows facing the social, political and cultural challenges of the 21st century. This article analyzes the evolution of the perception of 1st, 2nd and 3rd grade students compared to 4th, 5th and 6th grade students (6 to 13 years old), in the socio-political, socio-cultural, socio-affective and socio-economic dimensions of their citizenship training. The study had a qualitative approach, with an interpretative paradigm. Fifty-two interviews were conducted. The results show a progression in the understanding of the four dimensions evaluated, showing an increasingly broader and integrated perspective as the student’s advance in grade, which favors a gradual and reflexive construction from an early age.